An optical reaction micro-turbine - Silvio Bianchi (Nature Portfolio, 2018)
Light can be used to rotate micrometric turbines that usually rely on scattering to redistribute optical momentum and generate a mechanical torque. Here, 3D microfabricated light guiding structures can reroute an incoming flow of optical energy to generate a strong, uniform and controllable torque.